Strategic Development of the Brick Industry based on Islamic Economics: a Case Study in Bangko Bakti Village - Matondang, Seri Rezeki; Batubara, Chuzaimah; Daulay, Aqwa Naser (IAIN Manado, 2025)
This study aims to develop a strategic model for brick enterprise by integrating the SOAR framework with Islamic economic principles to enhance sustainability, ethical integrity, and long-term growth in small-scale industries. The research applies a qualitative descriptive method conducted in Bangko Bakti Village, Rokan Hilir Regency, Riau Province. Data were collected through in-depth interviews with the business owner, workers, and local stakeholders, complemented by field observations and secondary sources. Triangulation was used to ensure data reliability and validity, while the IFE–EFE matrices and SOAR analysis were applied sequentially to determine strategic positioning and formulate development strategies. Islamic values such as adl (justice), ihsan (excellence), amanah (trustworthiness), and maslahah (public welfare) were embedded in each analytical stage to guide ethical decision-making and ensure fairness in the business operations. The results show that the enterprise holds strong internal capabilities (IFE score 3.15) and favorable external opportunities (EFE score 3.00), positioning it in the “Grow and Build” quadrant of the IE matrix. Practical strategies derived from this integration include implementing digital marketing, improving production efficiency, ensuring quality control, and promoting fair wage distribution. The study demonstrates that incorporating Islamic ethics within the SOAR model can strengthen managerial accountability, social welfare, and stakeholder trust, offering a replicable approach for other SMEs seeking value-driven and sustainable growth.